The Repression of Atoh1 by Neurogenin1 during Inner Ear Development - Gálvez, Héctor; Tena, Juan J.; Giraldez, Fernando; Abelló, Gina (Frontiers in Molecular Neuroscience, 2017)
Atoh1 and Neurog1 are bHLH transcription factors crucial for the generation of hair cells (HCs) and neurons in the inner ear. Both genes are induced early in development, but the expression of Atoh1 is counteracted by Neurog1. As a result, HC development is prevented during neurogenesis. This work aimed at understanding the molecular basis of this interaction. Atoh1 regulation depends on a 3’Atoh1-enhancer that is the site for Atoh1 autoregulation. Reporter assays on chick embryos and P19 cells show that Neurog1 hampers the autoactivation of Atoh1, the effect being cell autonomous and independent on Notch activity. ATAC-seq analysis shows that the region B of the 3’Atoh1-enhancer is accessible during development and sufficient for both activation and repression. Neurog1 requires the regions flanking the class A E-box to show its repressor effect, however, it does not require binding to DNA for Atoh1 repression. This depends on the dimerization domains Helix-1 and Helix-2 and the reduction of Atoh1 protein levels. The results point towards the acceleration of Atoh1 mRNA degradation as the potential mechanism for the reduction of Atoh1 levels. Such a mechanism dissociates the prevention of Atoh1 expression in neurosensory progenitors from the unfolding of the neurogenic program.